Ethnopedagogical Approach In Educating Elementary School Students On The Implementation Of Clean And Healthy Behaviour - Gadis Niyanti Pertiwi; Shofi Zahra Agustina; Ila Rosmilawati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Kampung Naga is a traditional village that holds firm beliefs and adheres to the customs and philosophies mandated by its elders and rejects intervention from outside parties if it interferes with and damages the preservation of the village. In the field of health, the people of Kampung Naga prefer to use natural remedies as the first step and still believe in magical medicines, namely prayers performed by shamans or paraji. If the treatment does not work, they continue to medical treatment at the health centre or village midwife. In terms of Clean and Healthy Living Behaviour (PHBS), the people of Kampung Naga Tasimalaya still use flush toilets and have not used healthy latrine facilities. The purpose of this study examines the implementation of the ethnopedagogical approach in educational activities for the application of Clean and Healthy Living Behaviour (PHBS) in Kampung Naga Tasikmalaya as education for elementary schools, this approach considers cultural values and locality in Kampung Naga Tasikmalaya to increase students' understanding and participation in carrying out or implementing PHBS in their daily lives. The research method uses a descriptive qualitative approach. The collection techniques used were observation and literature study. The results showed that the ethnopedagogical approach can effectively increase awareness and implementation of PHBS, build student engagement, and create an inclusive learning environment through the local wisdom of the Tasikmalaya Naga village community.